2015
DOI: 10.1016/j.beth.2014.05.001
|View full text |Cite
|
Sign up to set email alerts
|

A Tangled Web: The Challenges of Implementing an Evidence-Based Social Engagement Intervention for Children With Autism in Urban Public School Settings

Abstract: There is growing evidence that efficacious autism-related interventions rarely are adopted or successfully implemented in public schools, in part because of the lack of fit between the intervention and the needs and capacities of the school setting. There is little systematic information available regarding the barriers to implementation of complex interventions such as those addressing social engagement for children with autism. The present study used fieldnotes from an implementation trial to explore barrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 38 publications
4
85
0
2
Order By: Relevance
“…Rather, Bottema-Beutel et al (2014) suggest that the number of observations required to produce reliable estimates may vary depending on the outcome measure and time point in the school semester. While behavioral observations serve as a gold standard for assessing children’s social engagement on the playground, they often are time intensive and costly to conduct (Locke et al, 2014). Future research should carefully consider increasing the number of observations to ensure reliability of the data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, Bottema-Beutel et al (2014) suggest that the number of observations required to produce reliable estimates may vary depending on the outcome measure and time point in the school semester. While behavioral observations serve as a gold standard for assessing children’s social engagement on the playground, they often are time intensive and costly to conduct (Locke et al, 2014). Future research should carefully consider increasing the number of observations to ensure reliability of the data.…”
Section: Discussionmentioning
confidence: 99%
“…Often teachers and parents have limited knowledge of what happens during recess. Teaching assistants rather than teachers often supervise recess, and parents are not present at school (Locke et al, 2015). …”
mentioning
confidence: 99%
“…This has the unintended consequence of reducing availability of mental health services in schools that desperately need them. Team members employed by community mental health agencies may have different training backgrounds, theoretical orientation, supervision requirements and sense of mission than those employed by the school district, which may lead to a fragmented system of care (Locke et al, 2015). …”
Section: Barriers and Recommendations For Ebp Implementation In Schoolsmentioning
confidence: 99%
“…Although only one study reported achieving above 80% implementation fidelity when school personnel implemented the intervention, the expectation of achieving 80% implementation fidelity, the level to which we train experts in clinic or university-based studies, in school or other community settings may not be realistic given the barriers and constraints (e.g., inexperienced and untrained school personnel, time, resources, etc.) to implementation observed in the school context (Locke et al, 2015). Perhaps engaging in the core components of the intervention or using certain evidence-based strategies as opposed to none is a sufficient catalyst for improvement in various social outcomes in schools and other community contexts.…”
Section: Discussionmentioning
confidence: 99%